Desentralisasi Fengelolaan Sumber Daya Alam di Riau; Strategi Impiementasinya - Ellydar Haidir (Fakultas Hukum Universitas Islam Indonesia, 2000)
An autonomy era has been lanched on January 1, 2001. It Is a sfating point for each district or province to enforce its resources. Riau as one of the provinces of the Republic of Indonesia, which has obtained an unfair treatment from the central goverment, must be ready to face the era with managing its rich natural resources effectively. However, in the use of the natural resources, Riau is necessary to have an appropriate implementation strafegy in order that the resources could be contonously utilized and directly enjoyed by all Riau's community.